Kra Canal (1824-1910): The Elusive Dream - Ngui Yew Kit, Clarence (Universiti Kebangsaan Malaysia, 2012)
Positioned in the north of the Malay Peninsula, the Isthmus of Kra is the narrowest land mass separating the Andaman Sea from the Gulf of Thailand. Cutting a canal across this isthmus – seldom more than 50 miles across – will reduce almost 1,500 miles of sea route between Europe and East Asia and offer a time saving of almost three days. Yet, what initially appears to be a logical and potentially profitable construction project has proven to be nothing more than an elusive dream. This article looks at the various proposals forwarded for The Kra Canal between 1824 and 1910, during the reigns of King Rama III Phra Nangklao, King Rama IV Mongkut and King Rama V Chulalongkorn. Coincidentally, these three eras represented the period of Siam's modernisation amid creeping European colonisation. These eras also showed Siam's different approaches to foreign relations: Phra Nangklao was an isolationist, Mongkut welcomed foreigners and Chulalongkorn was a fervent moderniser. In their different separate ways, all the three kings entertained various proposals to construct a canal across the Isthmus of Kra only to see to their failure of taking off beyond the planning stages. The insecurity of Siam's independence at the height of European colonialism in Southeast Asia was the penultimate reason for Siam's refusal to realise the Kra Canal dream.